Construction project scheduling and control - Mubarak, Saleh A. (Saleh Altayeb) (Pearson Prentice Hall, 2005)
For courses in Construction Management, Scheduling/Project Control in Civil/Construction/Engineering Technology. Written by a career construction professional, this text about scheduling and project control addresses the average student, detailing all the steps clearly and without shortcuts. Solved and unsolved exercises cover all subjects, computer software programs for construction are included, and presents precedence networks as the realistic solution to scheduling, the main part of project control.